1997
DOI: 10.1113/expphysiol.1997.sp004075
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death in bovine mammary tissue during lactation and involution

Abstract: SUMMARYCessation of milk removal causes mammary tissue involution, which in rodents is characterized by extensive tissue degeneration and loss of the majority of luminal epithelial cells by apoptosis. In contrast, bovine mammary tissue shows little histological evidence of tissue remodelling between lactations. In this study, we combined histology with molecular biology to examine the cellular and molecular changes in bovine mammary tissue on cessation of milking. Oligonucleosomal laddering of genomic DNA extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
2
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 32 publications
5
119
2
6
Order By: Relevance
“…For example, mRNA abundance of a-, b-and g-casein was observed to fall by up to 95% in rat mammary tissue within 24 h of litter removal (Travers et al, 1996), whereas the abundance of casein and a-lactalbumin mRNA was reduced in bovine mammary tissue 3 days after cessation of milk removal (Goodman and Schanbacher, 1991). Hence, after 7 days, a S1 -casein and a-lactalbumin mRNA were decreased by 85% and 99%, respectively (Wilde et al, 1997). The morphological changes in mammary tissue during the dry period in dairy animals are less pronounced and distinctly different compared with those seen during mammary involution in nonpregnant rodents.…”
Section: Altered Dry Periodsmentioning
confidence: 98%
See 3 more Smart Citations
“…For example, mRNA abundance of a-, b-and g-casein was observed to fall by up to 95% in rat mammary tissue within 24 h of litter removal (Travers et al, 1996), whereas the abundance of casein and a-lactalbumin mRNA was reduced in bovine mammary tissue 3 days after cessation of milk removal (Goodman and Schanbacher, 1991). Hence, after 7 days, a S1 -casein and a-lactalbumin mRNA were decreased by 85% and 99%, respectively (Wilde et al, 1997). The morphological changes in mammary tissue during the dry period in dairy animals are less pronounced and distinctly different compared with those seen during mammary involution in nonpregnant rodents.…”
Section: Altered Dry Periodsmentioning
confidence: 98%
“…The importance of the absence of prolactin and somatotropin (ST) for mammary gland involution has been shown in rodents (Marti et al, 1999) and has also been demonstrated for cows in vitro (Accorsi et al, 2002). A reduction in the circulating prolactin concentration was shown to accelerate mammary involution and the expression of insulin-like growth-factor binding protein 5 (IGFBP-5), which antagonizes the survival effects of IGF-I (Wilde et al, 1997 and. Moreover, MEC proliferation is stimulated by IGF-I in vitro (McGrath et al, 1991) and in vivo (Collier et al, 1993).…”
Section: Impact On Milk Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…At the initiation of lactation, the rapid increase to peak milk yield following parturition is primarily because of an increase in mammary epithelial activity in response to milking. The gradual decline in milk production following peak lactation is anomalous to gradual involution and is predominantly a result of mammary epithelial loss via apoptosis (Wilde et al, 1997;Capuco et al, 2001). Microarray studies on rodent (Master et al, 2002;Clarkson et al, 2004;Stein et al, 2004) and bovine (Suchyta et al, 2003;Singh et al, 2008) mammary tissues have identified multiple cell signalling pathways that may orchestrate the switch from a lactating to a nonlactating phenotype.…”
Section: Introductionmentioning
confidence: 99%